2018
DOI: 10.1002/pc.25142
|View full text |Cite
|
Sign up to set email alerts
|

Hyperelastic behavior and dynamic mechanical relaxation in carbon black‐polymer composites

Abstract: Tensile and thermo‐mechanical properties of nano‐composites fabricated by mechanically mixing semi‐crystalline ethylene‐co‐butyl acrylate (EBA) and carbon black (CB) nanoparticles are investigated. Stress–strain curves performed on samples over a broad range of CB content evidence the hyperelastic behavior of the EBA matrix. Neo‐Hookean and Mooney‐Rivlin models are used to fit the observed linear and nonlinear mechanical behaviors, respectively. The thermo‐mechanical curves highlight two relaxation phenomena d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…The low wear resistance of highly filled composite samples may be linked to their low toughness as it is deduced from the tensile properties performed on the current composite materials. Moreover, the increase of CB concentration leads to a large increase of the stiffness and to a reduction of the toughness . It is to be noticed that the lower deviation of H / E values for highly loaded composite samples indicates a good dispersion of CB throughout the polymer matrix confirming the same conclusions reported in our previous studies by using dielectric and mechanical analyses.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The low wear resistance of highly filled composite samples may be linked to their low toughness as it is deduced from the tensile properties performed on the current composite materials. Moreover, the increase of CB concentration leads to a large increase of the stiffness and to a reduction of the toughness . It is to be noticed that the lower deviation of H / E values for highly loaded composite samples indicates a good dispersion of CB throughout the polymer matrix confirming the same conclusions reported in our previous studies by using dielectric and mechanical analyses.…”
Section: Resultssupporting
confidence: 89%
“…Note that no correlation between the values of C l and the CB volume fraction is found for studied range of CB vol %. On the basis on the reported values obtained for both rubber and rigid polymers, we believe to observe of a decrease of C l with increasing the CB volume fraction because the CB particles increase the stiffness of the matrix . It might be prudent to take a definitive conclusion especially with few studies reported on the matter.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations